The Psychological Dynamics of Balinese Women as the Status of Wives Who Do Not Have Sons in Balinese Ethnic Hindu Marriages - I Gusti Agung Ayu Istri Sripradnya Paramita; Ni Nyoman Ari Indra Dewi; I Rai Hardika (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
The patrilineal system that the Indonesian people are interpreted that the structure of the kinship is based on the offline. Men's position also holds the right in the heirs. For the Bali Hindu family who has no boys raises concerns if there is no successor in the family to continue the duties and obligations of parents in the family and customs. So, bring up a psychological conflict in a wife who does not have a boy in his marriage. This study aimed to describe and explore the psychological dynamics experienced by a wife who has no boys at Balinese wine ethnic wedding. The method used in this research is qualitative method with case study approach. Data collection techniques utilized interviews, observation, and documentation performed towards Balinese women with the marriage status. This research focused on aspects of psychological dynamics including cognitive, affective, and associated. The results of the study showed that the occurrence of psychological changes in the wife who has no boy is from internal and external pressure or environment with cultural attribution and customs that are enacted by the people of Bali related to patrilineal kinship. The presence of self-awareness and acceptance, as well as the contribution of social support received by a wife who has no boy drafting on a positive psychological dynamic in cognitive, affective, and celibate cases can work properly.